Mechanisms of atrial fibrillation. Issue 24 (23rd August 2019) - Wijesurendra, Rohan S; Casadei, Barbara
Abstract : Atrial fibrillation (AF) is the most common sustained arrhythmia, currently affecting over 33 million individuals worldwide, and its prevalence is expected to more than double over the next 40 years. AF is associated with a twofold increase in premature mortality, and important major adverse cardiovascular events such as heart failure, severe stroke and myocardial infarction. Significant effort has been made over a number of years to define the underlying cellular, molecular and electrophysiological changes that predispose to the induction and maintenance of AF in patients. Progress has been limited by the realisation that AF is a complex arrhythmia that can be the end result of various different pathophysiological processes, with significant heterogeneity between individual patients (and between species). In this focused Review article, we aim to succinctly summarise for the non-specialist the current state of knowledge regarding the mechanisms of AF. We address all aspects of pathophysiology, including the basic electrophysiological and structural changes within the left atrium, the genetics of AF and the links to comorbidities and wider systemic and metabolic perturbations that may be upstream contributors to development of AF. Finally, we outline the translational implications for current and future rhythm control strategies in patients with AF.